Assessment of the accuracy of new and updated intraocular lens power calculation formulas in 10 930 eyes from the UK National Health Service. Issue 1 (January 2020) - Darcy, Kieren; Gunn, David; Tavassoli, Shokufeh; Sparrow, John; Kane, Jack X.
Abstract : Purpose: To compare the accuracy of new/updated methods of intraocular lens (IOL) power calculation (Kane, Hill-RBF 2.0, and Holladay 2 with new axial length adjustment) with that of established methods (Barrett Universal II, Olsen, Haigis, Holladay 1, Hoffer Q, and SRK/T). Setting: Bristol Eye Hospital, University Hospitals Bristol National Health Service, Foundation Trust, Bristol, UK. Design: Retrospective consecutive case series. Methods: Data from patients having uneventful cataract surgery with the insertion of 1 of 4 IOL types were included. Optimized IOL constants were used to calculate the predicted refraction of each formula for each patient. This was compared with the actual refractive outcome to give the prediction error. A subgroup analysis occurred based on the axial length and IOL type. Results: The study included 10 930 eyes of 10 930 patients with the Kane formula having the lowest mean absolute prediction error (MAE), which was statistically significant ( P < .001 in all cases) followed by the Hill 2.0, Olsen, Holladay 2, Barrett Universal 2, Holladay 1, SRK/T, Haigis, and Hoffer Q formula. The percentage of eyes predicted within ±0.5 D was Kane, 72%; Hill 2.0, 71.2%; Olsen, 70.6%; Holladay 2, 71%; Barrett 2, 70.7%; SRK/T, 69.1%; Haigis, 69%; and Hoffer Q, 68.1%. The Kane formula had the lowest MAE for short, medium, and long axial length subgroups and for each IOL type assessed. The updated versions of the Holladay 2 and Hill 2.0 formulas have resulted in improved accuracy. Conclusions: Overall and in each axial length subgroup, the Kane formula was more accurate than the other formulas. Abstract : In 10 930 patients, the Kane formula produced the most accurate results with the lowest mean absolute error, standard deviation of prediction error, and highest percentage of eyes within 0.25 D, 0.50 D, and 1.00 D.